Socializing the Use of Social Application Media in the Covid-19 Season Supporting the Activities of Hasanuddin Medan Helvetia Elementary School Teachers - Atika Aini Nasution; Baginda Harahap; Raflis Raflis (Abdimas Paspama, 2023)
Technology is very important in today's life, especially in the health system. Many medical equipment has been discovered that has a digital system, the aim of which is to make the work of doctors and nurses easier in treating patients. The world is currently faced with the problem of viruses that attack human health. The preventive solution that can be done as early as possible is to wear a mask, keep your distance, and maintain your health and wash your hands frequently. This is done so that bacteria and viruses are not transmitted from one person to another. Communication using WhatsApp is still not supported video conferencing for a participant capacity of up to hundreds of people, therefore we provide socialization on the use of video conferencing via internet-based applications. Thus, the Battuta University service team felt the need to conduct outreach in using more interactive applications to support long-distance communication for Hasanuddin Elementary School teachers. The results of community service achieved are that Hasanuddin Elementary School teachers are able to apply all applications that support holding open and closed meetings given the distance between teachers. It is hoped that the results of this counseling can support communication activities that are not limited in number or regional conditions.